Treatment of idiopathic pulmonary fibrosis: a position paper from a Nordic expert group. (13th November 2016) - Sköld, C. M.; Bendstrup, E.; Myllärniemi, M.; Gudmundsson, G.; Sjåheim, T.; Hilberg, O.; Altraja, A.; Kaarteenaho, R.; Ferrara, G.
Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal progressive lung disease occurring in adults. In the last decade, the results of a number of clinical trials based on the updated disease classification have been published. The registration of pirfenidone and nintedanib, the first two pharmacological treatment options approved for IPF, marks a new chapter in the management of patients with this disease. Other nonpharmacological treatments such as lung transplantation, rehabilitation and palliation have also been shown to be beneficial for these patients. In this review, past and present management is discussed based on a comprehensive literature search. A treatment algorithm is presented based on available evidence and our overall clinical experience. In addition, unmet needs with regard to treatment are highlighted and discussed. We describe the development of various treatment options for IPF from the first consensus to recent guidelines based on evidence from large‐scale, multinational, randomized clinical trials, which have led to registration of the first drugs for IPF.